Oxygenation of Hypoxic Coastal Baltic Sea Sediments Impacts on Chemistry, Microbial Community Composition, and Metabolism - Broman, Elias; Sachpazidou, Varvara; Pinhassi, Jarone; Dopson, Mark (Frontiers in Microbiology, 2017)
The Baltic Sea has undergone severe eutrophication during the last century, resulting in increased algal blooms and the development of hypoxic bottom waters. In this study, we sampled oxygen deficient sediment cores from a Baltic Sea coastal bay and exposed the bottom water including the sediment surface to oxygen shifts via artificial addition of air during laboratory incubation. Surface sediment (top 1 cm) from the replicate cores were sliced in the field as well as throughout the laboratory incubations and chemical parameters were analyzed along with high throughput sequencing of community DNA and RNA. After oxygenation, dissolved iron decreased in the water overlying the sediment while inorganic sulfur compounds (thiosulfate and tetrathionate) increased when the water was kept anoxic. Oxygenation of the sediment also maintained RNA transcripts attributed to sulfide and sulfur oxidation as well as nitrogen fixation in the sediment surface. Based on 16S rRNA gene and metatranscriptomic analyses it was found that oxygenation of the sediment surface caused a bloom of the Epsilonproteobacteria genus Arcobacter. In addition, the formation of a thick white film was observed that was likely filamentous zero-valent sulfur produced by the Arcobacter spp. Based on these results, sulfur cycling and nitrogen fixation that were evident in the field samples were ongoing during re-oxygenation of the sediment. These processes potentially added organic nitrogen to the system and facilitated the re-establishment of micro- and macroorganism communities in the benthic zone.